Pengembangan Instrumen Skala Berpikir Reflektif untuk Mengukur Level Kemampuan Berpikir Reflektif Mahasiswa Calon Guru Fisika - Sinensis, Arini Rosa; Firman, Harry; Hamidah, Ida; Muslim, Muslim (Universitas Nurul Huda, 2019)
The purpose of this study is to develop a reflective thinking scale instrument to measure the level of reflective thinking ability of prospective physics students. This research method used the DDR (Design Development Research) method with the Tools and Research model. The reflective thinking scale developed is a modification of the Reflective Thinking Kember which consists of 24 items each consisting of 6 definitions. The level of Kember reflective thinking namely; 1) Habitual Actions, 2) Understanding, 3) Reflective, 4) Critical Reflective. The research sample was 138 prospective physics teacher students who had taken thermodynamics courses. Data analysis techniques in this study used the CVR (Content Validity Ratio) for content validation analysis, Product Moment Correlation (construct validity test), Cronbach alpha (Reliability) and Confirmatory Factor Analysis to find a model match. The results show that the instrument is valid, reliable and the Goodness of Fit index. It is therefore denied that the instruments developed are valid, reliable and suitable for measuring the level of reflective thinking ability..